2018
DOI: 10.1021/acs.jpcc.8b03148
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Second Harmonic Sensing

Abstract: It has been recently suggested that the nonlinear optical processes in plasmonic nanoantennas allow for a substantial boost in the sensitivity of plasmonic sensing platforms. Here we present a sensing device based on an array of non-centrosymmetric plasmonic nanoantennas featuring enhanced second harmonic generation (SHG) integrated in a microfluidic chip. We evaluate its sensitivity both in the linear and nonlinear regime using a figure of merit (FOM = Δ � Δ ) that accounts for the relative change in the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Extended to the THz spectral region, the concept of nonlinear metasurfaces would allow to enrich the palette of sensors and coherent sources that are now available [Lee et al (2014)]. Finally, the enhanced nonlinear properties in metasurfaces could be exploited to further enhance the performances of sensing platforms with respect to those of simple dense arrays of nonlinear particles [Mesch et al (2016), Ghirardini et al (2018)], as we will describe in the next section.…”
Section: Please Cite This Article As Doi: 101063/50006093mentioning
confidence: 99%
“…Extended to the THz spectral region, the concept of nonlinear metasurfaces would allow to enrich the palette of sensors and coherent sources that are now available [Lee et al (2014)]. Finally, the enhanced nonlinear properties in metasurfaces could be exploited to further enhance the performances of sensing platforms with respect to those of simple dense arrays of nonlinear particles [Mesch et al (2016), Ghirardini et al (2018)], as we will describe in the next section.…”
Section: Please Cite This Article As Doi: 101063/50006093mentioning
confidence: 99%
“…We have also demonstrated that the response is conserved when the particles are embedded in biological media and the excitation beams are raster-scanned, two aspects essential for developing diagnostics and sensing schemes taking full advantage of the nonlinear sensitivity of the optical read-out. 44,45 Schanne-Klein, M.-C.; Beaurepaire, E. Imaging lipid bodies in cells and tissues using third-harmonic generation microscopy. Nature methods 2006, 3, 47-53.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] This decrease in the intensity of the SHG response reduces the interest in developing these particles for biological applications (e.g., bioimaging). 35,36 The SHG response of NLO particles can be signicantly enhanced by employing various strategies. 37 These approaches include the preparation of hybrid structures of the NLO material paired with plasmonic metals or organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…, bioimaging). 35,36 The SHG response of NLO particles can be significantly enhanced by employing various strategies. 37 These approaches include the preparation of hybrid structures of the NLO material paired with plasmonic metals or organic molecules.…”
Section: Introductionmentioning
confidence: 99%